2013
DOI: 10.1593/neo.13922
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Patient-Derived Human Pancreatic Tumor Xenograft Models for Preclinical and Translational Development of Cancer Therapeutics

Abstract: Preclinical evaluation of novel cancer agents requires models that accurately reflect the biology and molecular characteristics of human tumors. Molecular profiles of eight pancreatic ductal adenocarcinoma patient tumors were compared to corresponding passages of xenografts obtained by grafting tumor fragments into immunocompromised mice. Molecular characterization was performed by copy number analysis, gene expression and microRNA microarrays, mutation analysis, short tandem repeat (STR) profiling, and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
64
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 49 publications
11
64
1
1
Order By: Relevance
“…The AG-Br7 xenograft model was derived from a specimen of a patient with triple-negative breast cancer. AG-Panc4 was established from a patient with moderately differentiated adenocarcinoma of the pancreas (17). NCI-H322M lung adenocarcinoma cell line was used as a lung cancer model.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…The AG-Br7 xenograft model was derived from a specimen of a patient with triple-negative breast cancer. AG-Panc4 was established from a patient with moderately differentiated adenocarcinoma of the pancreas (17). NCI-H322M lung adenocarcinoma cell line was used as a lung cancer model.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Interestingly, these changes could not be reverted once the in vitro propagated cells were re-implanted into mice. Instead, PDTX retain the original tumor heterogeneity, thus allowing for clonal dynamic studies [6,25,30,[42][43][44][45][46]. Moreover, Eirew et al used deep genome and single cell sequencing methods to demonstrate an ongoing clonal selection in both primary and metastatic breast tumors, with the expansion of clones sharing recurrent patterns.…”
Section: Pdtx In Basic Cancer Research Modeling Tumor Heterogeneity Amentioning
confidence: 99%
“…40 Further recent work using exome sequencing has shown that along with the tumor architecture, the genetic signature is maintained for at least three passages, giving scope for greater investigation of prognostic biomarkers to therapeutic response. 41 This would ultimately reduce the requirement to perform PDX model testing for every individual and instead only require analysis of the primary tumor to direct therapy.…”
mentioning
confidence: 99%
“…PDX models are clearly showing promise as a valuable tool in evaluating the efficacy of novel treatments and have the advantage of recapitulating the natural genetic makeup of the original human patient tumor, even after passaging in vitro and in vivo, while allowing novel drug testing in an in vivo setting. 41,46 This provides valuable information that can go toward the design of more effective human clinical trials to further test novel treatments for cancers such as pancreatic cancer. 41 Although the use of PDX models in pancreatic cancer research is still relatively in its infancy, there are a number of studies that have utilized these models in testing the efficacy of novel drug leads against pancreatic cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation